THE RELATIONSHIPS LEARNING INTEREST, LEARNING CREATIVITY, AND PEER INTERACTION WITH MATH STUDENTS LEARNING OUTCOMES IN CLASS VIII OF MTs MUHAMMADIYAH KARANGKAJEN - Dilla Restianola; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The result of low mathematics students learning related to several factors. Self-confidence, learning discipline, and the use of learning resources is some of the factors related to learning outcomes. This research aims to determine the presence or absence of a positive and significant relationship among self-confidence, learning discipline, and use of learning resources with mathematics learning outcomes in students class VIII of even Semester of MTsN Yogyakarta II  academic year of 2015/2016. The population in this study was the woman students of grade VIII in MTsN  Yogyakarta II academic year 2015/2016, which was divided into 4 classes, namely VIII D, VIII E, VIII F, VIII G totaling 137 students. Samples were taken in class VIII E as a research class sample and with a random sampling technique to the class. Data were collected by the questionnaire method and test method. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, the test of linearity, and the test of independence. Analysis of the data for testing hypothesis using correlation analysis and linear regression analysis. The results showed that there is a positive and significant relationship among self-confidence, learning discipline, and use of learning resources with mathematics learning outcomes students class VIII of even Semester in MTsN Yogyakarta II  academic year of 2015/2016. It is showed by Fcount =  Ftable = 2.9011 with R = 0.511998  and R2 = 0.2621 with , with SR = 30.7344 , SR = 18.5067% ,and SR = 50.75895% SE = , SE = and SE = 13.3060524 %.